FUNCTIONS, FUNCTIONING AND OPTIMIZED POSITIONING OF PRESSURE CONTROL VALVES IN OIL-HYDRAULIC CIRCUITS - Reis, M. N. E.; Tavares, S. G.; Soares, C. B.; Soares, J. A.; Antunes, R. H. R.; Fossa, C. H. L.; Monteiro, P. R. (Revista de Engenharia Térmica, 2006)
The pressure control valves can perform different functions in the hydraulic systems, such as: establish maximum pressure, reduce pressure in some circuit lines, and establish sequence movements, among other functions. The main operation of these valves consists of providing a balance between pressure and the force load on a spring. Most of these valves can be positioned in many different levels, between totally open and totally closed, depending on the flow and on the pressure differential. The pressure control valves are usually named according to their primary functions, e.g., lock wire valve, sequence valve, safety valve, etc. and, their basic function is limit or to determine the pressure of the hydraulic system for the attainment of a certain function of the equipment in motion. They are also classified by the type of connections, by the size and by the selected pressure band. Instead of relief and security, discharge, counterbalance, sequence, reducing and shock suppressor valves represent the pressure control devices. In this paper, oil-hydraulic circuits are suggested for practical lessons of Hydraulic and Pneumatic Commands where they regulate valves of pressure, by acting in the following situations: limiting the maximum pressure of the system, determining a level of pressure, determining two different levels of pressure, determining at the same time two distinct levels of pressure, unloading the pump. The functions of these devices will be discussed and analyzed as an attempt to improve their position in the circuit.